Gender differences in robotic surgery for rectal cancer: A retrospective study - Muhammad Ali; Wei Wang; Liuhua Wang; Bin Liu; Jun Ren; Daorong Wang (Intelligent Surgery)
Objective: To investigate gender-based differences in outcomes following robotic surgery for rectal cancer. Methods: A retrospective study was conducted on 155 patients (82 males, 73 females) who underwent robotic surgery for rectal cancer. Demographic, pre-operative, operative, and post-operative data were collected and analyzed. Results: There were no significant differences in demographic and pre-operative characteristics between genders. While males had longer operative times (177 ​min vs. 160 ​min for females), this was not statistically significant. However, males had significantly shorter hospital stays (P ​< ​0.05), while females had a higher incidence of Clavien-Dindo grade III-IV complications (48% vs. 37.8% in males). Complication rates were comparable, but specific complications varied between genders. Conclusion: Demographic and pre-operative features were similar, notable differences between genders emerged in operative time, length of hospital stay and complication severity. These findings underscore the importance of gender-specific considerations in both surgical approaches and post-operative care for rectal cancer patients undergoing robotic surgery.